Methodology for Applying Augmented Reality in the Teaching of Computer Architecture - Brum, Luciano Moraes da Luz; Pinho, Leonardo Bidese de; Camargo, Sandro da Silva (International Journal of Computer Architecture Education, 2015)
This work aims to use Augmented Reality (AR) technology for visualizing a model of the Neander architecture and to verify the effectiveness of this tool as a facilitator for student learning in the field of Computer Architecture. With AR technology, it is possible to provide students with a visual sense of the interaction between a computer's internal components. Using markers, students can interact with the application, encouraging active learning. This technology is expected to improve student performance by making them more engaged in the teaching-learning process and providing them with a more solid understanding of the internal workings of computers, thus enhancing their performance in introductory Computer Architecture courses.